Architecture oriented otherwise - Leatherbarrow, David (Princeton Architectural Press, 2009)
"Renowned writer and thinker David Leatherbarrow argues for a richer and more profound, but also more rational, way of thinking about architecture, namely on the basis of how it performs. Not only how it functions, but how it acts, "its manner of existing in the world," including its effects on the observers and inhabitants of a building as well as on the landscape that situates it. In the process, Leatherbarrow transforms our way of discussing buildings from a passive technical or programmatic assessment to an active and engaged examination of the lives and performances of buildings, intended and otherwise."--BOOK JACKET.